Perlakuan Akuntansi Agrikultur Berbasis Maqashid Al-Syariah - Saiful Muchlis; Suhartono Suhartono; Husnul Khotimah (LPPM ISNJ Bengkalis, 2021)
The purpose of this study was to determine how the quality of financial statement information on PT. Perkebunan Nusantara XIV is seen from biological assets recognition, measurement, and disclosure in terms of concept maqashid al-sharia and PSAK 69. This type of research is qualitative research with an interpretive paradigm approach. The results showed that PT. Perkebunan Nusantara XIV, in terms of recognition, measurement, and disclosure of biological assets, was by the applicable standards, namely the statement of PSAK 69: Agriculture. With the accounting treatment of biological assets following the applicable PSAK, the quality of financial statement information becomes relevant and reliable so that it makes it easy for users to understand financial statements. Especially for management, it can be used as the basis for making the right decisions. Judging from the concept of maqashid al-sharia, researchers have not been able to reveal the overall implementation of this concept in the work environment of PT. Perkebunan Nusantara XIV. Nevertheless, in applying the maqashid al-shariah concept, the head of the accounting and reporting division has implemented managing biological assets and preparing financial reports so that the financial reports are relevant and reliable.